The agreement between GMFCS and GMFCS-E&R in children with cerebral palsy. (September 2013) - Gudmundsson, Caroline; Nordmark, Eva
Abstract: Aims: The aims of this study were to examine the agreement between the original Gross Motor Function Classification System (GMFCS) and the revised version, GMFCS-E&R, and to describe the characteristics of the persons who changed level when the GMFCS-E&R classification was used. Methodology: During 2009 there were 706 persons (aged 1–20 years) with cerebral palsy (CP), living in the southernmost part of Sweden, who participated in a secondary prevention follow-up programme for persons with CP. Of the 706 participants, 561 were assessed by physiotherapists using both GMFCS and GMFCS-E&R. The agreement between 665 assessment forms, including both GMFCS and GMFCS-E&R levels, was analysed. Descriptive, unweighted and weighted Kappa statistics were used. Major findings: The absolute agreement, with corresponding levels according to GMFCS and GMFCS-E&R was 96.8% ( n = 644). Unweighted Kappa showed K = 0.96 (95% confidence interval: 0.94–0.98) and weighted Kappa showed K = 0.97 (95% confidence interval: 0.96–0.99). Both were interpreted as an agreement corresponding to an "almost perfect agreement". Principal conclusion: This study suggests that the GMFCS-E&R, if administrated carefully, could be used when comparing longitudinal data with the GMFCS.